THE VALUE PROPOTITION CONCEPT IN HIGHER EDUCATION : HOW TO BUILD HYBRID CURRICULA UNIVERSITAS CIPUTRA CULINARY BUSINESS - Eric Harianto; Fabiola Leoparjo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The culinary industry is one of the sectors that support the economy in Indonesia. Even during the COVID-19 pandemic where the average industry experienced a decline, the culinary industry was able to survive with a digitalization strategy. Study program Tourism Culinary Business is a study program at Ciputra University to create Culinary Entrepreneurs. One of the methods used to generate innovation is to examine the teaching products offered through the Value Proposition Canvas. The purpose of establishing this VPC specifically for Culinary Business is to prepare CB to face the transformation of digital education in accordance with the direction of online learning from the temporary government or hybrid system in the future. This research uses Creswell Data analysis technique (2014) and is conducted for two years starting from January 2018 to Desember 2020. Method used in this research is qualitative descriptive method with informants consisting of 8 internal resource persons consisting of lecturers, staff and 15 external speakers consisting of active students and alumni. Data testing is carried out using the data triangulation method. The results of this study are: From the use of the VPC framework, Culinary Business can analyze consumer profiles to find out what problems or expectations are expected to be obtained as prospective Culinary Entrepreneurs. This consumer profile can be resolved by the formation of a value map that maps the solutions and added value offered to form educational service products with a new system, from being completely offline to a hybrid or mixed system. Keywords: Culinary Business, Higher Education, Hybird Curricula, Value Propotition